2009
DOI: 10.1530/rep-09-0009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active immunization against growth differentiation factor 9 and/or bone morphogenetic protein 15 on ovarian function in cattle

Abstract: Growth differentiation factor 9 (GDF9) and bone morphogenetic protein 15 (BMP15) are essential for ovarian follicular growth in sheep, whereas only GDF9 is essential in mice suggesting that the roles of these oocyte-derived growth factors differ among species. At present, however, there is only limited information on the action of BMP15 and GDF9 in other species. Thus, the aim of this experiment was to determine the effect of neutralizing GDF9 and/or BMP15 in vivo on ovarian follicular development and ovulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 30 publications
4
42
0
Order By: Relevance
“…Four mares in this group had only one or no ovulations, whereas mares with several ovulations had a relatively greater incidence of abnormally small follicles from which there were ovulations. This is similar to reports by Juengel et al (2009) where it was reported that some vaccinated cattle failed to have ovulations, while the animals with multiple ovulations appeared to have ovulations from smaller than average follicles. In deer immunized against BMP15, ovulation rate (as indicated by fawns/doe born) was increased over three breeding seasons even though animals had a significant immune response.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Four mares in this group had only one or no ovulations, whereas mares with several ovulations had a relatively greater incidence of abnormally small follicles from which there were ovulations. This is similar to reports by Juengel et al (2009) where it was reported that some vaccinated cattle failed to have ovulations, while the animals with multiple ovulations appeared to have ovulations from smaller than average follicles. In deer immunized against BMP15, ovulation rate (as indicated by fawns/doe born) was increased over three breeding seasons even though animals had a significant immune response.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, altered ovarian activity and decreased ovulation rates suggest that antibodies created in response to immunization were effective in binding and inactivating the BMP-15 protein in mares. Results of the present study for BMP-15 treatment are similar to those reported in other BMP-15 immunization studies in sheep and cattle, with an overall decrease in ovulations and some animals having a complete cessation of ovulations (Juengel, 2002;Juengel et al, 2009Juengel et al, , 2004McNatty et al, 2007). Four mares in this group had only one or no ovulations, whereas mares with several ovulations had a relatively greater incidence of abnormally small follicles from which there were ovulations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite such limitations, our results indicates that the concentrations of E 2 and P in follicular fluid of large, medium and small follicles had no significant difference, which suggests that CART has no direct regulatory effect on the production of these two hormones in porcine antral follicles. Follicular growth and development are regulated by endocrine factors [40,41], including E 2 and P, which are important indicators to reflect the state of follicular growth. Smith et al [12] demonstrated that CART had an inhibitory effect on in vitro production of E 2 by granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…In sheep and cattle, immunization against GDF-9 and BMP-15, alone or together, showed that GDF-9 and BMP-15 were associated with corpus luteum activity Juengel et al 2009). Similar to the report from Silva et al (2005) that GDF-9 was observed in goat corpus lutea, we found that both GDF-9 and BMP-15 presented in corpus lutea of adult human.…”
Section: Discussionmentioning
confidence: 99%